Anti-proliferative effect of novel primary cetyl alcohol derived sophorolipids against human cervical cancer cells HeLa - Nawale, Laxman; Dubey, Parul; Chaudhari, Bhushan; Sarkar, Dhiman; Prabhune, Asmita (Plos One, 2017)
Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to display anticancer activity. In the present study, we report anti-proliferative studies on purified forms of novel SLs synthesized using cetyl alcohol as the substrate (referred as SLCA) and their anticancer mechanism in human cervical cancer cells. Antiproliferative effect of column purified SLCA fractions (A, B, C, D, E and F) was examined in panel of human cancer cell lines as well as primary cells. Among these fractions, SLCA B and C significantly inhibited the survival of HeLa and HCT 116 cells without affecting the viability of normal human umbilical vein endothelial cells (HUVEC). The two fractions were identified as cetyl alcohol sophorolipids with non-hydroxylated tail differing in the degree of acetylation on sophorose head group. At an IC50 concentration SLCA B (16.32 mu g ml(-1)) and SLCA C (14.14 mu g ml(-1)) blocked the cell cycle progression of HeLa cells at G1/S phase in time-dependent manner. Moreover, SLCA B and SLCA C induced apoptosis in HeLa cells through an increase in intracellular Ca2+ leading to depolarization of mitochondrial membrane potential and increase in the caspase-3, -8 and -9 activity. All these findings suggest that these SLCAs could be explored for their chemopreventive potential in cervical cancer.

Isolation and characterization of chitosans from different fungi with special emphasis on zygomycetous dimorphic fungus benjaminiella poitrasii: evaluation of its chitosan nanoparticles for the inhibition of human pathogenic fungi - Mane, Shamala; Pathan, Ejaj; Tupe, Santosh; Deshmukh, Sneha; Kale, Deepika; Ghormade, Vandana; Chaudhari, Bhushan; Deshpande, Mukund (Biomacromolecules, 2022)
The cell wall chitosan was extracted from fungi belonging to different taxonomic classes, namely, Benjaminiella poitrasii (Zygomycetes, dimorphic), Hanseniaspora guilliermondii, Issatchenkia orientalis, Pichia membranifaciens, and Saccharomyces cerevisiae (Ascomycetes, yeasts), and Agaricus bisporus and Pleurotus sajor-caju (Basidiomycetes). The maximum yield of chitosan was 60.89 ± 2.30 mg/g of dry mycelial biomass of B. poitrasii. The degree of deacetylation (DDA) of chitosan extracted from different fungi, as observed with 1H NMR, was in the range of 70–93%. B. poitrasii chitosan exhibited the highest DDA (92.78%). The characteristic absorption bands were observed at 3450, 1650, 1420, 1320, and 1035 cm–1 by FTIR. Compared to chitosan from marine sources (molecular weight, MW, 585 kDa), fungal chitosans showed lower MW (6.21–46.33 kDa). Further, to improve the efficacy of B. poitrasii chitosan (Bp), nanoparticles (Np) were synthesized using the ionic gelation method and characterized by dynamic light scattering (DLS). For yeast and hyphal chitosan nanoparticles (BpYCNp and BpHCNp), the average particle size was <200 nm with polydispersity index of 0.341 ± 0.03 and 0.388 ± 0.002, respectively, and the zeta potential values were 21.64 ± 0.34 and 24.48 ± 1.58 mV, respectively. The B. poitrasii chitosans and their nanoparticles were further evaluated for antifungal activity against human pathogenic Candida albicans ATCC 10231, Candida glabrata NCYC 388, Candida tropicalis ATCC 750, Cryptococcus neoformans ATCC 34664, and Aspergillus niger ATCC 10578. BpHCNps showed lower MIC90 values (0.025–0.4 mg/mL) than the chitosan polymer against the tested human pathogens. The study suggested that nanoformulation of fungal chitosan, which has low molecular weight and high % DDA, is desirable for antifungal applications against human pathogens. Moreover, chitosans as well as their nanoparticles were found to be hemocompatible and are therefore safe for healthcare applications.

Development of novel ssDNA aptamers for detection of receptor-binding domain of SARS-COV-2 - Auti, Amogh; Yadav, Pranay; Bodkhe, Rahul; Bhandari, Yogesh; Varma, Sanjana; Chaudhari, Bhushan; Rahi, Shraddha; Ghormade, Vandana; Vamkudoth, Koteswara Rao (ACS Omega, 2025)
The highly virulent and transmissible SARS-CoV-2 causes COVID-19 and poses a global public health threat. Herein cloned, expressed, and the molecular weight of the receptor-binding domain (RBD) of the SARS-CoV-2 gene encoding protein was confirmed by SDS-PAGE electrophoresis and Western blot analysis. The pivotal aim is to develop single-stranded DNA (ssDNA) aptamers for the rapid detection of SARS-COV-2 infections in humans. In this investigation, a library of nine novel ssDNA aptamers was developed by several rounds of systematic evolution of ligands by an exponential enrichment approach and assessed by an enzyme-linked aptamer assay for binding affinity against RBD antigen (Ag). An in vitro assay resulted in a varied colorimetric signal that depends on the nature of aptamer. Quantitative determination of AptRBD3, AptRBD6, and AptRBD8 aptamers exhibited excellent binding affinity against Ag in the range of 5-10 ng/mL. The putative AptRBD3, AptRBD6, and AptRBD8 aptamers were converted into peptide sequences and docked against RBD, exhibiting good binding energy of -6.8, -6.3, and -7.1 kcal/mol respectively, which were recorded. Furthermore, docking studies of ssDNA aptamers were performed using HDOCK web server to ascertain the binding mechanism and docking score perceived as -389.74, -404.28, and -390.37. Despite this, we engineered a high-affinity AptRBD3.3 aptamer that formed a single and bulged loop, which improved binding affinity, resulted in a docking score of -361.56, and exhibited sensitivity at 4 ng of Ag of SARS-CoV-2. Moreover, computational modeling of AptRBD3.3 revealed an intriguing significant binding affinity with the RBD mutant SARS-CoV-2 S-UK variant (PDB ID: 7EDG) with a docking score of -350.21. In conclusion, the AptRBD3.3 aptamer can be used for the development of lateral flow device and electrochemical sensors for rapid, low-cost, and accurate detection of COVID-19 infection in humans for point of care diagnostics.